2020
DOI: 10.26480/taec.02.2020.67.69
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Planting Time and Variety on the Growth and Yield of Tomato

Abstract: The experiment was conducted at the RARS, Jamalpur during rabi 2019-2020 to find out the suitable planting time and increase production and economic return. Tomato variety viz. V1 = BARI Tomato-14, V2 = Udyan were considered as factor A and five sowing dates viz. S1 = 25 August, S2 = 15 September, S3 = 05 October, S4 = 25 October, S5 = 15 November considered as factor B. The experiment was laid out in RCBD (Factorial) with three replications. The yield of tomato was significantly affected by different sowing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Hilborn et al [23] reported that heat stress significantly affects the yield and fruit quality of tomato. The plant height of tomato affected by seedling transplanting dates and genotypes [11,21]. The maximum plant height was observed after first transplanting that was done in 18…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hilborn et al [23] reported that heat stress significantly affects the yield and fruit quality of tomato. The plant height of tomato affected by seedling transplanting dates and genotypes [11,21]. The maximum plant height was observed after first transplanting that was done in 18…”
Section: Discussionmentioning
confidence: 99%
“…Transplanting periods have a significant relation with local climatic variability. Different transplanting dates and varieties have significant effect on the yield of tomato [11]. Plant maturity, harvesting date, yield, and crop quality can be affected by transplanting date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation